PRELIMINARY STUDY ON THE EFFECT OF VITAMIN C ON THE GROWTH AND SURVIVAL RATE OF THE FRESHWATER PRAWN (Macrobrachium rosenbergii) LARVAE - Ikhsan Khasani (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2008)
This experiment was conducted to investigate the influence of vitamin C on growth and survival rate of freshwater prawn larvae. The treatment dosages of vitamin C were 0.0, and 0.75 mg/L. Each treatment was in triplicates and arranged in a complete randomized design. Vitamin C was given to the larval rearing media every three days. Larvae were cultured in six conical fibreglass tanks of 50 L volume installed in a fibreglass tank (2 m x 0.8 m x 0.8 m) filled with water for temperature stabilizer. Each conical tank was stocked with 6,500 larvae (nauplii). Artemia nauplii were given on D3 and egg custard as artificial feed on D9. Larval rearing was done for 25 days in constant temperature (29oC–31oC) using automatic heater. Statistical analysis showed that metamorphosis speed of larvae was significantly affected by adding of vitamin C (P<0.05), but survival rate was similar (P>0.05). Addition of vitamin C also resulted in a better growth of freshwater prawn larvae.